Postharvest Technology of Button Mushroom: A Socio-Economic Feasibility - Kumar, Santosh; Chand, Gireesh; Srivastava, J N; Ahmad, Md Shamsher (Journal of Postharvest Technology, 2014)
Fresh mushroom is highly perishable and deteriorates immediately after harvest. It develops brown colour on the surface of the cap due to the lyses of cell and enzymatic action of polyphenol oxidase that results in shorter shelf life. Being highly perishable in nature, the fresh mushrooms need to be processed to extend the off-season availability by adopting appropriate postharvest technology and processing into value-added products. The value-added products are the need of the hour for the mushroom growers not only to reduce the losses but also to enhance the income by value-addition to boost the consumption of mushroom. The possible value-added products can be developed either by converting freshly harvested mushrooms into ketch-up, murabba, candy, chipsand pickles or by dehydrating freshly harvesting mushrooms into dehydrated form and then making soup powder, biscuit, nuggets and Ready–to–eat mushroom curry (RTE). This review article summarizes the information regarding postharvest technologies and value addition of fresh mushroom generally followed worldwide.